Dominica Agriculture and LULUCF Inventory needs assessment country profile - Vásquez, Daniela; Barrios, Julián; Haynes, Connor (Bioversity International and International Center for Tropical Agriculture, 2025)
The agriculture and land use, land-use change, and forestry (LULUCF) sectors are key determinants of greenhouse gas (GHG) emissions in Latin America and the Caribbean (LAC), both because of their importance in national economies and because of their weight in the climate commitments made under the Paris Agreement. In this context, moving towards more refined methodologies, such as those of Levels 2 and 3 established in the Intergovernmental Panel on Climate Change (IPCC) Guidelines, is essential to improve transparency, reduce uncertainty in national inventories, and support more ambitious and effective mitigation policies. The Monitoring, Reporting, and Verification (MRV) system has evolved as the main monitoring mechanism under the United Nations Framework Convention on Climate Change (UNFCCC). From the initial obligation to submit national inventories, to the introduction of “measurable, reportable, and verifiable” commitments at COP13 in Bali, and with the establishment of the Enhanced Transparency Framework (ETF) in the Paris Agreement (2015), countries have been consolidating their reporting and quality control capacities. This framework establishes processes that ensure the comparability and verifiability of information, and also incorporates accountability for financing, technology, and capacity building. Taken together, the results presented constitute a technical baseline that describes the current state of MRV systems for agriculture and LULUCF in the region. This assessment provides evidence to guide the improvement of national inventories, facilitate the transition to higher-level methodologies, and reduce the uncertainty associated with emissions estimates, thus contributing to the robustness and consistency of reports under the ETF.